Let $x>0$, $y>0$ and $z>0$. Show that $$x^3y+y^3z+z^3x\ge xyz(x+y+z).$$

I known we can't WLOG: $x\ge y\ge z$, if this, I can use rearrangement inequality, But other I can't it. Thanks?

  • $\begingroup$ Suppose for the time being $x\ge y\ge z$. Now observe that, $$\begin{align}(x^3y-x^2yz)+(y^3z-xy^2z)+(z^3x-xyz^2)&=x^2(xy-yz)+y^2(yz-zx)+z^2(zx-xy)\\&=(x^2-z^2)(xy-yz)+(y^2-z^2)(yz-zx)\\&=y(x^2-z^2)(x-z)+z(y^2-z^2)(y-z)\\&\ge0\end{align}$$To justify the last step we use the assumption that $x\ge y\ge z$ and the hypothesis that $x,y,z>0$. The other cases may be dealt in a similar manner. $\endgroup$ – user 170039 Aug 28 '17 at 15:42

You can not assume $x\geq y\geq z$ because our inequality is cyclic and not symmetric,

but we can say that $(x^2,y^2,z^2)$ and $\left(\frac{1}{x},\frac{1}{y},\frac{1}{z}\right)$ are opposite ordered.

Thus, by Rearrangement $$x^3y+y^3z+z^3x=xyz\left(\frac{x^2}{z}+\frac{y^2}{x}+\frac{z^2}{y}\right)=$$ $$=xyz\left(x^2\cdot\frac{1}{z}+y^2\cdot\frac{1}{x}+z^2\cdot\frac{1}{y}\right)\geq$$ $$\geq xyz\left(\frac{x^2}{x}+\frac{y^2}{y}+\frac{z^2}{z}\right)=xyz(x+y+z).$$

C-S also works because $$\sum_{cyc}\frac{x^2}{z}\geq\frac{(x+y+z)^2}{x+y+z}=x+y+z,$$ but you wanted Rearrangement.

We can prove this inequality also by $uvw$, AM-GM, BW and more.

  • $\begingroup$ so How to use Rearrangement? $\endgroup$ – wightahtl Aug 28 '17 at 14:20
  • $\begingroup$ care to explain the first inequality? $\endgroup$ – windircurse Aug 28 '17 at 14:22
  • $\begingroup$ I have use C-S by solve it,because $\sum \dfrac{z^2}{x}\sum x\ge (\sum x)^2$ $\endgroup$ – wightahtl Aug 28 '17 at 14:26
  • $\begingroup$ @wightahtl windircurse I added something. I hope now it's clear. $\endgroup$ – Michael Rozenberg Aug 28 '17 at 14:27
  • 1
    $\begingroup$ I believe @user170039 was trying to ask why you cannot assume $x\ge y\ge z$, though the sum of your responses have only come of the form that you don't need them, which doesn't answer the question at all. $\endgroup$ – Simply Beautiful Art Aug 28 '17 at 20:40

I don't know what is meant by rearrangement, so I'll offer another solution, fairly basic, but it works. $$x^3y+y^3z+z^3x \geq xyz(x+y+z)$$ $$xy(x^2)+yz(y^2)+zx(z^2) - xyz(x+y+z) \geq 0$$ $$xy(x^2-2xz+z^2)+yz(y^2-2yx+x^2)+zx(z^2-2yz+y^2) \geq 0$$ $$xy(x-z)^2 + yz(y-x)^2+zx(z-y)^2 \geq 0$$ The last line consists of all positive values, and thus we can work backwords and show this inequality to be true.

  • $\begingroup$ Rearrangement Inequality. $\endgroup$ – user 170039 Aug 28 '17 at 14:29
  • $\begingroup$ Thanks! I will go learn about that now. $\endgroup$ – Isaac Browne Aug 28 '17 at 14:29
  • $\begingroup$ @Isaac Browne Your proof it's just AM-GM, which I meant: $\sum\limits_{cyc}(x^3y+z^2xy)\geq\sum\limits_{cyc}\left(2\sqrt{x^3y\cdot z^2xy}\right)=2\sum\limits_{cyc}x^2yz$. $\endgroup$ – Michael Rozenberg Aug 28 '17 at 14:40
  • $\begingroup$ @MichaelRozenberg Thanks for that, $(x-y)^2 \geq 0$ is indeed equivalent to AM-GM. I just like to think of this as more fundamental as we see all the positive values on one side being greater than 0. $\endgroup$ – Isaac Browne Aug 28 '17 at 14:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.